Literature Review Journal: HR Planning, HR Development and Compensation, Employee Performance - Waliyati, Waliyati; Supratikta, Hadi (Formosa Journal of Applied Sciences, 2024)
From the results of previous research, it is very relevant that employee performance is influenced by HR planning, HR development and compensation. These findings indicate that HR planning, HR development and compensation have a positive impact on employee performance. HR planning that is integrated with a culture of learning and talent retention can improve employee performance. Apart from that, providing fair compensation also plays an important role in improving employee performance. The importance of effective HR management in improving employee performance is demonstrated by this research. The practical implication of this research is that, in order for employee performance to increase overall, companies must focus on HR planning, HR development and compensation.